Bioreactor-based mass production of human iPSC-derived macrophages enables immunotherapies against bacterial airway infections. Issue 1 (December 2018) - Ackermann, Mania; Kempf, Henning; Hetzel, Miriam; Hesse, Christina; Hashtchin, Anna; Brinkert, Kerstin; Schott, Juliane; Haake, Kathrin; Kühnel, Mark; Glage, Silke; Figueiredo, Constanca; Jonigk, Danny; et al.
Abstract The increasing number of severe infections with multi-drug-resistant pathogens worldwide highlights the need for alternative treatment options. Given the pivotal role of phagocytes and especially alveolar macrophages in pulmonary immunity, we introduce a new, cell-based treatment strategy to target bacterial airway infections. Here we show that the mass production of therapeutic phagocytes from induced pluripotent stem cells (iPSC) in industry-compatible, stirred-tank bioreactors is feasible. Bioreactor-derived iPSC-macrophages (iPSC-Mac) represent a highly pure population of CD45+ CD11b+ CD14+ CD163+ cells, and share important phenotypic, functional and transcriptional hallmarks with professional phagocytes, however with a distinct transcriptome signature similar to primitive macrophages. Most importantly, bioreactor-derived iPSC-Mac rescue mice fromPseudomonas aeruginosa -mediated acute infections of the lower respiratory tract within 4-8 h post intra-pulmonary transplantation and reduce bacterial load. Generation of specific immune-cells from iPSC-sources in scalable stirred-tank bioreactors can extend the field of immunotherapy towards bacterial infections, and may allow for further innovative cell-based treatment strategies. Pulmonary infections constitute a substantial health problem worldwide. Here the authors show that phagocytes similar to primitive macrophages can be generated from human induced pluripotent stem cells, by the use of industry-compatible, stirred-tank bioreactors, and applied as a cell-based therapy to treat acute bacterial infections in mice.